2020
DOI: 10.1080/2162402x.2020.1782575
|View full text |Cite
|
Sign up to set email alerts
|

The role of circulating monocytes and JAK inhibition in the infectious-driven inflammatory response of myelofibrosis

Abstract: Myelofibrosis (MF) is characterized by chronic inflammation and hyper-activation of the JAK-STAT pathway. Infections are one of the main causes of morbidity/mortality. Therapy with Ruxolitinib (RUX), a JAK1/2 inhibitor, may further increase the infectious risk. Monocytes are critical players in inflammation/immunity through cytokine production and release of bioactive extracellular vesicles. However, the functional behavior of MF monocytes, particularly during RUX therapy, is still unclear. In this study, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
(101 reference statements)
0
25
0
Order By: Relevance
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After we excluded the irrelevant manuscripts based on the screening of their titles and abstracts ( n = 81), we examined the full texts of 33 manuscripts. Finally, after we applied the exclusion and inclusion criteria, 27 original articles were included in this review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed studies investigated the levels of cell-free DNA ( n = 1), extracellular vesicles ( n = 7), microparticles ( n = 14) or circulating endothelial cells ( n = 5) levels in MPNs. Flow cytometry was by far the most employed method of detection ( n = 23) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The evidence of immunological dysregulation in PMF derives also from the murine Gata1 low mouse model, which shows a high level of TGF-β1 and collagen in megakaryocytes and abnormal signature in TGF-β1 signaling gene expression in spleen and marrow [ 34 , 35 , 36 ]. The dysregulation of immune system in MPNs stems, in part, from the defective differentiation of monocytes into dendritic cells [ 37 ] and from their inability to produce and release cytokines, such as IL-1β, TNF-α, IL-6 and IL-10, in response to infectious stimulus and to migrate into damaged tissues [ 38 , 39 ].…”
Section: Mpns As Inflammatory Diseasesmentioning
confidence: 99%
“…Also, we recently demonstrated that circulating monocytes from JAK2 V617F-mutated MF patients are dysregulated and show a reduced in vitro ability to produce/secrete inflammatory cytokines in response to an infectious stimulus. Surprisingly, the JAK1/2 inhibitor Ruxolitinib promotes the EV-based inflammatory cytokine signaling [ 116 ].…”
Section: The Immune Evasion Mechanism Of Blood Cancers: Focus On Ementioning
confidence: 99%